Sex Education Through Reproductive System Materials on Body Privacy Awareness of Elementary/MI Students: A Systematic Review (2022-2024) - Ika Wahyuningsih; Fatiya Sakinah; Nur Syahriani; Asih Widi Wisudawati (Elementary Teacher Education Program, Majalengka University, 2025)
Sexual violence that occurs against children of various ages is still a global issue that is rampant in various countries. Schools as official educational institutions should provide facilities related to sexual education from an early age. This review uses the Systematic Literature Review (SLR) method, aiming to explore relevant literature to understand how sex education can be applied systematically and its impact on the body privacy awareness of elementary/middle school students.), covering five stages, namely; determine eligibility criteria, define information sources, literature selection, data collection, data item selection. 28 articles were obtained from Google Scholar and Scopus searches that met the criteria and will be analyzed. The results of the review show that sex education is important to teach to children from an early age. Of the 28 articles, 5 of them clearly mentioned in their research findings related to the urgency of child sex education. Various unique ways have been tested and researched to implement ideal sexual education in elementary schools, including psychoeducation, voicing media posters sex education based on audio visual and touch sensors, WiseBook, digital story media, and comics. Efforts to provide an understanding of body boundaries have also begun to be made, such as through role play and service-learning methods. However, only one study was found related to learning the human reproductive system, which showed that the results were not optimal. The lack of visual appeal in the teaching materials makes learning less interesting and tends to be boring.